Extract of Meretrix meretrix Linnaeus induces angiogenesis in vitro and activates endothelial nitric oxide synthase - 刘明 魏鉴腾 王惠 丁丽丽 张玉艳 林秀坤 (Chinese journal of oceanology and limnology, 2012)
Meretrix meretrix Linnaeus has long been used as traditional Chinese medicine in oriental medicine. The angiogentic activity of the extract of M. meretrix was investigated in this study, using human umbilical vein endothelial cells （HUVECs）. Extract ofM. meretrix Linnaeus （AFG-25） was prepared with acetone and ethanol precipitation, and further separated by Sephadex G-25 column. The results show that AFG-25 promoted proliferation, migration, and capillary-like tube formation in HUVECs, and in the presence of eNOS inhibitor NMA, the tube formation induced by AFG-25 is inhibited significantly. Moreover, AFG- 25 could also promote the activation of endothelial nitric oxide synthase （eNOS） and the resultant elevation of nitric oxide （NO） production. The results suggested that M. meretrix contains active ingredients with angiogentic activity and eNOS/NO signal pathway is in part involved in the proangiogenesis effect induced by AFG-25.